(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The purpose of the investigation was to identify aflatoxin B1 (AFB1) in the blood serum and seminal fluid of 50 of patients from Iraqi male who suffering from infertility include (oligozoospermia, asthenozoospermia and teratozoospermia) with 16 fertile males as control depending on seminal fluid profile examination. The HPLC technique was used for AFB1 detection of the samples (serum and semen). The results showed that all the patient and control were gave positive detected of AFB1 50/50 (100%) and 16/16 (100%) respectively, in the serum at mean (81.08 ±3.95) ng/ml at range (114-60) and (8.31 ±0.63) ng/ml at range (5-12), respectively. Also detected AFB1 in the seminal fluid of patients at mean 39/50(78%) ng/ml at range (37-0), but not appear of AFB1 in any sample of control. There were highly significant differences (P≤0.01) between the mean level of AFB1 in the infertile male patients and control.